2020
DOI: 10.3389/fimmu.2020.589010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TLR7 Polymorphisms on the Susceptibility and Progression of HIV-1 Infection in Chinese MSM Population

Abstract: Toll-like receptor (TLR) 7 plays a key role in innate and adaptive immunity for HIV-1 infection. We evaluated the effect of TLR7 polymorphisms on disease susceptibility and progression of HIV-1 infection in Chinese MSM (men who have sex with men). Blood samples were taken from 270 patients with laboratory confirmed HIV infection, 196 male controls were tested, and three TLR7 intronic polymorphisms (rs179010-C > T, X:12884766; rs2074109-T > C, X:12885330; and rs179009-A > G, X:12885361) were analyzed by PCR-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…TLR7 gene is located on the X-chromosome 13 , which carries multiple polymorphisms potentially associated with human disease, including susceptibility and progression of HIV-1 infection, asthma, autoimmune thyroiditis, systemic lupus erythematosus (SLE) 14 17 . The rs3853839 C/G single-nucleotide polymorphism (SNP), which is located in the 3′ untranslated region of the TLR7, has been associated with an increase in TLR7 mRNA and protein expression, as well as upregulation of idiopathic subglottic stenosis (iSGS) 18 20 .…”
Section: Introductionmentioning
confidence: 99%
“…TLR7 gene is located on the X-chromosome 13 , which carries multiple polymorphisms potentially associated with human disease, including susceptibility and progression of HIV-1 infection, asthma, autoimmune thyroiditis, systemic lupus erythematosus (SLE) 14 17 . The rs3853839 C/G single-nucleotide polymorphism (SNP), which is located in the 3′ untranslated region of the TLR7, has been associated with an increase in TLR7 mRNA and protein expression, as well as upregulation of idiopathic subglottic stenosis (iSGS) 18 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies in humans have pointed to a role for TLR SNPs, especially TLR7, in HIV infection and their association with viral loads. The presence of the most frequent TLR7 polymorphisms, TLR7 Gln11Leu (rs179008), was associated with increased viral load and altered CD4 T cell counts during HIV infection [53,54] while polymorphisms in TLR7 (re179010) and TLR8 (rs3764880) may reduce the risk of disease by participating in inhibition of viral load leading to the slower progression of infection [28,55,56]. Our results revealed that 9 out 14 identified polymorphisms were significantly associated with the SRLVs proviral concentration.…”
Section: Discussionmentioning
confidence: 72%
“…It has been found that genetic variants of TLRs can be associated with different outcome of several diseases [15,25]. Polymorphisms within TLR7 and TLR8 have been linked to susceptibility and progression of different viral diseases including these caused by Human Immunodeficiency virus (HIV-1), Hepatitis C virus (HCV), Chikungunya virus (CHIKV) and Crimean-Congo hemorrhagic fever (CCHF) virus [26][27][28][29]. Mikula et al [30,31] suggested that mutations in TLR7, TLR8 and TLR9 may play an important role as host factor predisposing sheep for infection with SRLVs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 35 ] The susceptibility, severity, and prognosis of bacterial meningitis in children and nonsmall cell lung cancer have also been proven to be related to this factor. [ 36 , 37 ] Case-control studies and meta-analyses considering TLR7 also confirmed that its polymorphism is related to the characteristics of a large number of diseases, especially immune-related diseases such as HIV-1 [ 38 ] and HBV [ 39 ] infection, tuberculosis, [ 17 ] asthma, [ 40 ] systemic lupus erythematosus, [ 41 ] and many types of cancer. [ 42 , 43 ] The main possible mechanisms were also associated with changes in dsRNA-binding capacity and inflammatory factor production related to signaling pathways, mainly NF-κB and MAPK.…”
Section: Discussionmentioning
confidence: 94%